'This industry lives on gossip and scandal': female star narratives and the Marilyn Monroe biopic. Issue 4 (2nd October 2017) - Cohan, Steven
ABSTRACT: This article discusses the migration of the female star narrative, a staple of the backstudio picture during the studio era, from theatrical fictional films to biopics on cable and broadcast TV. I focus in particular on the cycle of Marilyn Monroe biopics, which has served as a primary means by which Hollywood now makes female stardom legible as a narrative, one that disregards the star's talent and hard work while emphasising her glamour and erotic value on one hand and her pathology and abjection on the other. The Monroe biographies stand out from those about celebrities in other professions or one-offs about other female stars because their sheer number over the past several decades gives them a coherence of their own as a cycle of biopics that, for all their claims of factuality, follow conventions of those older star narratives built around fictional protagonists. The cycle thus reiterates an anachronistic impression of stardom that disavows female labour while perpetuating the mystique of Hollywood in ways that are consistent with the industry's masculinist biases and anxieties about female stardom.